THE FACTORS IN INTENTION TO DO WHISTLEBLOWING - Menhard, Menhard; Safrizal, Safrizal (Pattimura Proceeding, 2023)
Introduction/Main Objectives: Whistleblowing means information by an employee believed to be related to violations of laws, regulations, codes of conduct, professional speech, or procedural errors, corruption, abuse of authority, or threats to public safety and workplace safety. It is an act of disclosure. Background issue: Corruption is a big concern, but not all can be solved. Novelty: While whistleblowing investigations are typically conducted in the private sector, in this case the whistleblowing investigation is more recent as it is conducted in the government sector. Research method: This study is a quantitative study of all regional tissue populations and uses a targeted sampling technique using criteria. The main sources of research data are distribution of questionnaires and reference books and academic papers. The analysis used to test the data is multiple linear regression. Findings/Results: The results of this study show that individual cost variables, fraud severity, and organizational commitment influence intentions to take whistleblowing actions. Conclusion: Based on the discussion in the study, we can conclude that whistleblowing is an important study in the government sector, influenced by personal cost factors, fraud severity, and organizational commitment